Analysis of Digital Financial Literacy of Gen Z Muslims - Farida Nursjanti; Lia Amaliawiati; Irma Nilasari (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2023)
Effective usage of digital financial services requires an extensive knowledge of digital finance. Combining both digital and financial knowledge, digital financial literacy is a skill set. For financial consumers, digital financial services offer opportunities as well as difficulties. While the adoption of sophisticated technology-based financial goods poses obstacles, there are also potential for tailored financial products and services, quicker transactions, and simple access to financial products. The purpose of this study is to test and analyze several aspects of Gen Z Muslim financial literacy as well as to ascertain how socio-demographic factors relate to that literacy. One-Way Anova and difference tests were used for the data analysis. Based on the study's findings, it can be said that Gen Z Muslims do not differ in their level of digital financial literacy based on gender. The Self-Determination to Use the Knowledge and Skill aspect of digital financial literacy among Gen Z Muslims has the lowest level, while the Digital Knowledge aspect has the highest level, when compared on the basis of gender. Based on age, the lowest level of digital financial literacy for Gen Z Muslims is in the Financial Knowledge aspect, while the highest level of digital financial literacy for Gen Z Muslims is in the Digital Knowledge aspect. The younger respondents of generation Z Muslims have lower levels of digital financial literacy, it was also found. From the results of the One-Way Anova test, it was concluded that there were differences in the digital financial literacy of Gen Z Muslims based on age.